The Role of Teacher Interaction and Self-Directed Learning on High School Students' Online Learning Satisfaction - Muhibbin, Maulana Arif; Wulandari , Primatia Yogi; W, Danan Satrio (Procedia of Social Sciences and Humanities, 2024)
The aim of this study is to examine how high school students' satisfaction with online learning is impacted by instructor involvement and self-directed learning. A quantitative methodology was employed, involving 340 pupils from five different Surabaya schools. Random cluster sampling with stratified sampling was the method used. The learner-instructor interaction questionnaire by Kang and Im (2014), the student satisfaction with online learning scale adopted from Dziuban et al. (2015), and the self-rating scale of self-directed learning derived from Sulasiwi et al. (2019) are the measuring tools used in this research. With a value (R Square) of 0.401, the regression test results indicate that student satisfaction with online learning is significantly influenced by both teacher interaction and self-directed learning. Self-directed learning provided 0.233 and instructor interaction contributed 0.454, respectively, to the total. Teachers should be able to acquire excellent communication skills in this way in order to teach. In addition, counseling sessions are held for students to help them become self-sufficient in their online education. It is well established that students who engage positively with teachers and who possess strong self-directed learning skills would be more satisfied with their online education, which leads to in online learning success.